Robot Navigation Control System Using HMC5883L - Asti Riani Putri; Putri Nurrahayu; Anwar Anas (Department of Electrical Engineering ITS and FORTEI, 2019)
In the development of technology, the increasingly rapid world of robotics is also very much needed in helping everyday life, for example to move goods, technology that is so rapid requires the world of education to carry out development in various fields of science. Where the nation's next generation enhances science and technology so as not to be left behind by other nations, this study was conducted in order to be able to obtain robotic navigation according to their needs, the purpose of this study is to make robots with autonomous navigation and not affected by temperature or obstacles in front of it because it is equipped with an ultrasonic sensor that functions as a proximity sensor so that it does not affect the obstacles in front while for HMC5883l it is used to determine the angle corresponding to the object, the method used in programming robots still uses logic control programs and combined with the formula used in sensor measurements HMC5883l. The results of the research conducted are that the robot can move according to predetermined data input.Keywords: HMC58831, navigation, robot.